Mixed-Method Study Analysing Lessons Learned From ACTIVE-AGE@home: BRIDGE Recruitment Model to Engage Frail Older Adults in Intervention Trials (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Multicomponent physical activity programmes can prevent frailty in older adults but remain underutilised. To increase adoption, healthcare policy must prioritise research on preventive strategies. Although randomised controlled trials (RCTs) and clinical trials (CTs) are essential, recruitment challenges often lead to underpowered studies, wasted resources, and unexpected costs. Transparent and comprehensive reporting on recruitment is rare. This study aimed to develop effective strategies for engaging frail older adults in trials by analysing recruitment efforts and outcomes from the ACTIVE-AGE@home trial.Method: A mixed-method study was conducted to evaluate recruitment strategies at three levels: macro (broad-scale), meso (community-level), and micro (individual-level). Quantitative analysis assessed the effectiveness of these strategies, while qualitative data – field notes documenting researchers’ recruitment experiences – were analysed using thematic analysis (TA) following Braun and Clarke’s approach. Both a deductive TA, guided by the TIBaR model (Trust, Incentives, Barriers, and Responsiveness), and an inductive approach were employed to explore motivations for long-term engagement, adherence, and maintenance.Results: Over six months, researchers contacted 49 macro-, 112 meso-, and 1,001 micro-level recruitment partners. Of these, 30 meso- and 44 micro-level partners referred frail older adults. Micro-level referrals were most effective, yielding 23 eligible participants, compared to six via meso-level. Thematic analysis identified four key themes: 1) Be appealing – Make the study unique, accessible, and approachable. 2) Foster reciprocal relationships – Build trust and shared ownership with recruitment partners. 3) Understand identity – Consider the identities of both recruitment partners and potential participants. 4) Gear trial requirements – Align study design with recruitment realities and identity needs.Conclusion: Micro-level strategies, particularly personal contact and warm referrals through local healthcare and welfare professionals, are critical for recruiting frail older adults. Macro- and meso-level strategies should support these efforts. The BRIDGE model emerged from this analysis, offering a reflective tool balancing recruitment, identity, and trial demands. As rigid RCT designs present recruitment barriers, more flexible trial designs should be explored. Transparent reporting of both successes and challenges is essential to improve future intervention research.Support/Funding Source: This work is supported by Research Foundation Flanders, under Applied Biomedical Research with a Primary Social finality (Grant Number: T002322N).